IMPLEMENTASI MODEL SEM PADA HUBUNGAN IPM, IPD DAN IDM - Pardomuan Robinson Sihombing; Ade Marsinta Arsani; Widdia Angraini; Wisnu Pratiko (Jurnal Bayesian : Jurnal Ilmiah Statistika dan Ekonometrika, 2022)
This study aims to determine the influence of the Human Development Index (HDI), poverty and village funds on Village Development approached with the Village Development Index (IPD) and the Building Village Index (IDM). The data used is published data from the Ministry of Villages PDTT and the Central Statistics Agency in 2018. The analysis model used is the Structural Equation Model (SEM) model. The results of the village fund hypothesis test have not had a direct effect on IPD and have not had an indirect effect on IDM. The poverty rate has a significant negative effect directly on IPD and indirectly affects IDM, as well as HDI has a significant positive effect on IPD and indirectly affects IDM. IPD has a significant positive effect directly on IDM. A comprehensive and targeted policy is needed so that village development can take place in a sustainable manner. In addition, supervision is needed related to the use of village funds so that they are right on target in developing villages